2016
DOI: 10.1016/j.seizure.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiepileptic drug on thyroid hormones in patients with epilepsy: A meta-analysis

Abstract: Our study suggests that use of AEDs such as CBZ, PHT, and VPA, was associated with alteration of thyroid hormones among patients with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 59 publications
3
30
0
3
Order By: Relevance
“…Also, the results showed that patients receiving carbamazepine had the lowest T3, T4, and FT4 levels than patients receiving other AEDs. These results agree with the results reported by Zhang et al 10 and Abobker et al 12 Two possible explanations for this result include carbamazepine-accelerated metabolism of thyroid hormones through induction of the hepatic P 450 enzyme system, and interference with thyroid hormone competitive binding to thyroid-binding globulin. 9 Our results partly agree with those of Elmasry et al 17 who conducted a study on 30 children with epilepsy and 15 healthy control children and reported lower FT4 level in epileptic patients, while no significant difference was found in TSH levels between patients and controls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, the results showed that patients receiving carbamazepine had the lowest T3, T4, and FT4 levels than patients receiving other AEDs. These results agree with the results reported by Zhang et al 10 and Abobker et al 12 Two possible explanations for this result include carbamazepine-accelerated metabolism of thyroid hormones through induction of the hepatic P 450 enzyme system, and interference with thyroid hormone competitive binding to thyroid-binding globulin. 9 Our results partly agree with those of Elmasry et al 17 who conducted a study on 30 children with epilepsy and 15 healthy control children and reported lower FT4 level in epileptic patients, while no significant difference was found in TSH levels between patients and controls.…”
Section: Discussionsupporting
confidence: 93%
“…In studying the effect of Na valproate on thyroid function, we found lower serum levels of T3, T4, and higher TSH levels in patients with epilepsy in comparison with the control group and no significant difference in FT4 between the two groups. These results agreed with both Zhang et al 10 and Yılmaz et al 11 who showed the same results. Also, Abobker et al 12 studied thyroid dysfunction in children with epilepsy and its association with AEDs in Sudanese children.…”
Section: Discussionsupporting
confidence: 92%
“…The only correlation observed between AED blood levels and thyroid hormone levels was a significant negative correlation between the CBZ blood level and fT4 level (p=0.016). In the literature, findings regarding the effect of VPA on thyroid function are inconsistent; some studies reported an association between VPA and increased thyroid hormone levels, whereas others reported lowered levels or no effect at all (15)(16)(17)(18). The effect of VPA on serum thyroid hormone levels could not be fully explained.…”
Section: Discussionmentioning
confidence: 98%
“…The effect of VPA on serum thyroid hormone levels could not be fully explained. Studies on the effect of VPA on the thyroid hormones showed different results, an association between VPA and decreased and increased hormones levels has been reported by different studies (15)(16)(17)(18). It has been reported that VPA may affect thyroid hormone levels due to its enzymatic inhibitory effect rather than the induction of microsomal enzymes in the liver (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation